Plasma soluble urokinase-type plasminogen activator receptor level is independently associated with coronary microvascular function in patients with non-obstructive coronary artery disease. Issue 1 (March 2015) - Mekonnen, Girum; Corban, Michel T.; Hung, Olivia Y.; Eshtehardi, Parham; Eapen, Danny J.; Al-Kassem, Hatem; Rasoul-Arzrumly, Emad; Gogas, Bill D.; McDaniel, Michael C.; Pielak, Tomasz; Thorball, Christian W.; Sperling, Laurence; et al.
Abstract: Background : Soluble urokinase-type plasminogen activator receptor (suPAR) is a novel biomarker released from leukocytes and endothelial cells that has been associated with atherosclerotic cardiovascular disease. We hypothesized that plasma suPAR level is an independent predictor of coronary microvascular function. Methods : Coronary blood flow velocity and plasma suPAR levels were evaluated in patients with non-obstructive coronary artery disease. Coronary flow reserve (CFR) was calculated as the ratio of hyperemic to basal average peak blood flow velocity and coronary microvascular dysfunction was defined as CFR ≤ 2.0 in the setting of a fractional flow reserve value of ≥0.75. Plasma suPAR levels were measured using ELISA technique. The association between suPAR and CFR was investigated using univariate and multivariate regression analyses. Results : In 66 patients, 47% were men, 26% had diabetes, 68% had hypertension and 76% had dyslipidemia. Mean age was 55 ± 12 years and median suPAR level 2.82 (2.08–3.40) ng/mL. Plasma suPAR levels correlated with age (r = 0.31, p = 0.01), body mass index (r = 0.25, p = 0.04) and high-sensitivity C-reactive protein (hs-CRP) (r = 0.33, p = 0.009). While median suPAR level was not significantly different in patients with different cardiovascular risk factors, patients on statin therapy had significantly higher suPAR level (p = 0.03). SuPAR correlated negatively with CFR and, after multivariate adjustment for established cardiovascular risk factors, medications profiles and hs-CRP, suPAR remained an independent predictor of CFR (B = −0.30, p = 0.04), indicating an independent association between suPAR level and coronary microvascular function. Conclusions : In this cross-sectional study, plasma suPAR level was an independent predictor of coronary microvascular function. Larger prospective clinical trials are warranted to investigate the prognostic value of this novel biomarker and the role of immune dysregulation in coronary microvascular disease. Highlights: SuPAR is a novel inflammatory and immune biomarker associated with atherosclerosis. We prospectively evaluated 66 patients with non-obstructive coronary artery disease. SuPAR correlated inversely with coronary flow reserve (r = −0.30, p = 0.04). High suPAR level is an independent predictor of coronary microvascular function.